Qualidade física, compartimentos de carbono e sua simulação com o modelo Century em um argissolo coeso sob integração lavoura-pecuária no cerrado maranhense - Barbosa, Leovanio Rodrigues (2021)
The aim of this study was to evaluate soil quality through studies of physical attributes, organic matter and to model carbon and nitrogen with the Century v.4.5 simulator in areas under conservation systems in cohesive soils in the cerrado of eastern Maranhão. An area under exclusive use in no-tillage for fourteen years, three areas under no-tillage with different years (2, 4 and 8), of entry into crop-livestock integration rotation, and an area under native vegetation of the Cerrado Biome were selected. The physical and physical-hydric attributes studied were: soil density, porosity (total, macro and micro), penetration resistance, water retention curve and available water capacity. Organic matter was evaluated using total organic carbon, chemical and physical fractionation, microbial biomass carbon, total nitrogen and carbon and nitrogen stocks. To carry out the simulations with the Century model, an area under exclusive use in no-tillage (PD), one under rotational no-tillage with subsoiled croplivestock integration (PD-ILP) was selected, as well as an area under native cerrado. The carbon (C) and nitrogen (N) simulations considered real and future scenarios with management changes. Soil samples were collected in layers from 0.00-0.10; 0.10-0.20; 0.20- 0.30 and 0.30-0.50 m being used in the evaluations of physical attributes and organic matter. In the area under exclusive use in PD, there was a loss of physical quality attributed to higher values of resistance to penetration, lower porosity, and low soil water retention. Furthermore, it had lower C content and stocks. The chemical fractionation of C revealed superior humin content in detriment to fulvic and humic acid fractions. For the physical fractionation of C, there were no differences in particulate organic C values between the areas studied, but higher values of C associated with minerals were observed in areas with a recent history of ILP. The adoption of ILP in a PD system also showed gains in the values of water retention capacity and availability to plants. For the modeling study, the model simulated with greater precision the stabilization of the C stock in detriment of the N stock. area under exclusive use in PD. In future scenarios, the adoption of the PD system rotated every four years with corn and pasture revealed greater efficiency in the capacity of total organic carbon (TOC) and total nitrogen (NT) stocks. As for the scenarios created in the area under PD rotated with ILP, the maintenance of the PD system rotated every four years with ILP subsoiled showed higher COT stocks. The difference in C and N stocks between future scenarios in this area did not exceed 1.8 Mg ha-1 for TOC and 0.48 Mg ha-1 for NT. The adoption of the PD system, with rotation every four years with corn and pasture, was the management that best provided C and N stocks